2020
DOI: 10.3126/kumj.v18i1.33342
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug Resistant and Extended Spectrum β-lactamase Producing Salmonella Species Isolated from Fresh Chicken Liver Samples

Abstract: Background Emergence of antibiotic resistance among microbes contaminating the fresh meat products is a global public health concern as they can be easily transmitted to humans through their consumption and contact. Objective The current study was conducted to determine the distribution of antimicrobial resistance among Salmonella species isolated from fresh chicken liver samples with special emphasis on extended spectrum beta-lactamase (ESBL) production. Method A total of 200 fresh chicken liver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Although ESBL was discovered several decades ago, there have been troublesome to sort out organisms that are responsible for ESBL production due to several reasons such as difficulty in its detection and variability during reporting [7]. A large number of studies have reported the presence of ESBL producers in clinical [8][9][10] as well as nonclinical samples [11][12][13]. Nevertheless, some studies concluded E. coli and K. pneumoniae as the most crucial bacteria responsible for ESBL production [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although ESBL was discovered several decades ago, there have been troublesome to sort out organisms that are responsible for ESBL production due to several reasons such as difficulty in its detection and variability during reporting [7]. A large number of studies have reported the presence of ESBL producers in clinical [8][9][10] as well as nonclinical samples [11][12][13]. Nevertheless, some studies concluded E. coli and K. pneumoniae as the most crucial bacteria responsible for ESBL production [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Spread plate technique was performed using Plate count agar, Eosin Methylene Blue (EMB) agar and Xylose Lysine Deoxycholate (XLD) agar. The plates were aerobically incubated for 24 h at 37 °C and CFU/mL was determined [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm-producing bacteria, according to infectious disease experts at the Centers for Disease Control and Prevention (CDC), could be responsible for 65% of all bacterial infections, compared to their free-floating counterparts [ 26 ]. Most importantly, production of biofilm, ESBL and MBL confer E. coli [ 14 , 27 ] as well as Salmonella [ [28] , [29] , [30] , [31] ] with increased resistance towards an array of antibiotics; thereby, contributing to failures in the treatment of several infections.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on the prevalence of Salmonella in poultry giblets obtained from slaughterhouse or retail stores; 2.2-59.40% of the livers ( Telli et al, 2018 ; Jung et al, 2019 ; Procura et al, 2019 ; Yüksel et al 2019 ; Adhikari et al 2020 ; Liu et al, 2020 ; Tohamy et al, 2022 ; Abdelhamed et al, 2023 ); 0 to 5% of hearts ( Acaröz et al, 2018 ; Telli et al, 2018 ); 8.10% of spleen samples ( Alcantara et al, 2022 ); and 0 to 20% of the gizzards ( Acaröz et al, 2018 ; Telli et al, 2018 ; Raji et al, 2021 ; Tohamy et al, 2022 ) were found to harbor the pathogen. When the studies involving serotyping were examined, the most frequently identified Salmonella serovars were reported as Enteritidis, Typhimurium, Virchow, Infantis, Schwarzengrund and Kentucky.…”
Section: Introductionmentioning
confidence: 99%